Electrochemical assessment of corrosion-fatigue degradation stages - Simões, Alda Maria Pereira (2022)
ABSTRACT: The study is focussed on the joint effect of corrosion and mechanical cyclic stresses observed on mooring chains of Floating Production Storage and Offloading (FPSO) units. The tests were performed using grade R4 steel in artificial sea water, under stress-controlled and fully reversed loading. The corrosion-fatigue degradation was monitored using open circuit potential measurements simultaneously with the cyclic mechanical load. The open circuit potential response varies during the corrosion-fatigue test, depending on the stage of degradation of the material. This technique has proven to be capable of identifying important phenomena, such as crack initiation and crack propagation, on the material under corrosion-fatigue loading condition.